IMPROVING COMMUNICATION CAPABILITY ASK FOR AUTISM CHILDREN THROUGH MEDIA PECS BASED ANIMATED PICTURE - Sattriedi Wahyu Binabar; Taryadi Taryadi; Dicke JSH. Siregar (JAICT, 2020)
The number of children suffering from autism from year to year is increasing. Autism Spectrum Disorders (ASD) is autism that occurs in childhood in the form of disorders characterized by disorders that affect language and communication, imagination and flexibility of thought and socialism. One way to improve communication skills, especially the ability to ask is to use the help of computer software. In this study, the PECS (Picture Exchange Communication System) method with the help of animation to attract the attention of ASD children. The results obtained were an increase of 70% communication ability to request from ASD children who were the object of research.